Visualising migration: Online tools for taking us beyond the static map. (10th March 2015) - Dennett, Adam
Abstract : This review tours some of the growing number of online tools that have been developed with modern web technologies to present complex migration data matrices in visually appealing and communicative ways. The tour highlights some of the real benefits that dynamic visualisations can bring to conveying detailed information, but also shows where success can be contingent on the choices made by developers on the relative importance of spatial, temporal and attribute information and how this is represented on the screen.